Reality–proof activity scheduling for energy–efficient wireless sensor networks. (20th March 2014) - Beaudaux, Julien; Gallais, Antoine; Noël, Thomas
A straightforward idea to prolong wireless sensor networks network lifetime is to schedule activities of nodes, that will turn into either Active or Passive states during the deployment. Several papers proposed solutions to turn Passive a large subset of nodes. However, only few of those provide information on how to translate this activity state in reality. In this paper, we further improved several activity scheduling mechanisms by introducing a new activity state called Sensing–Only. This new sensor node state concerns formerly Active nodes, all the more reducing the size of this subset. In addition, radio usage being the sensor nodes main source of energy depletion, we also provide a realistic translation of activity states by adjoining to each of those a specific configuration of the medium access control layer. Finally, we validate our approach both by simulation and experimentation over a large set of real sensor nodes.